PENGARUH RISIKO USAHA BERBASIS INFORMASI AKUNTANSI TERHADAP PREMIUM PENERBITAN SAHAM PERDANA DI INDONESIA - Melisa Marianni Manampiring; Dewi Ratnaningsih (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2013)
The purpose of this research is to examine the impact of accounting-based business risks in prospectus to IPOissue premium in Indonesia Capital Market (IDX). Proxies for accounting-based business risks are age of thecompany, company’s size, liquidity, after tax earnings, leverage, and IPO’s offering size.Sample of this research consists of 35 rms listed in Indonesia Capital Market (IDX) that went public during2009 to 2010. Data for this research are taken from Pusat Referensi Pasar Modal (PRPM) located in IndonesiaCapital Market (IDX). This research found that after tax earnings and IPO’s offering size are statisticallysigni cant in determining IPO issue premium.Kewords: issue premium, accounting-based business risks, age of the company, company’s size, liquidity,after tax earnings, leverage, and IPO’s offering size.